Synthesis, Structure and Magnetic Characterization of Orthoferrite LaFeO3 Nanoparticles - Abbas, Yehia Mohammed; Mansour, Ahmed Bakry; Ali, Shehab Esmail Mohammed; Abdel-Hamid, Ahmed Hassan Ibrahim (JOURNAL OF ADVANCES IN PHYSICS, 2018)
Single-phase lanthanum orthoferrite (LaFeO3) was prepared by an auto-combustion method. The analysis of synchrotron room temperature X-ray diffraction (XRD) data confirmed the orthorhombic LaFeO3 perovskite of space group Pnma without any impurity phase. The Scherrer's formula and Williamson-Hall plot based on XRD data were employed to estimate the crystallite size of the prepared sample. For a deeper insight into the crystal structure, high-resolution transmission microscopy imaging (HRTEM) was performed. The estimated values of crystallite size from HRTEM and synchrotron XRD data were coincident. The HRTEM images confirmed the polycrystalline nature of the prepared sample through the obvious lattice planes which are related to (121) plane. Furthermore, the M(H) hysteresis loop of the investigated sample was characterized by a vibrating sample magnetometer (VSM). The magnetic properties obtained through analyzing the magnetization versus temperature M(T) and magnetization versus magnetic field M(H) curves indicated that LaFeO3 possessed weak ferromagnetism at room temperature.